Huolong pot comprehensive moxibustion combined with Chinese herbal medicine wound dressing and TDP electromagnetic wave irradiation in the treatment of stage 4 pressure injuries in a patient with multiple injuries and complete paraplegia (火龙罐综合灸联合生肌玉红膏换药和特定电磁波谱照射治疗1例多发伤并完全性截瘫伴4期压力性损伤患者的护理) - YAN Shaolin (颜少林); XIE Lihong (谢利红); HE Yalian (何亚莲) (Journal of International Translational Medicine Limited, 2024)
This paper summarized the Huolong pot comprehensive moxibustion combined with Chinese herbal medicine wound dressing and TDP electromagnetic wave irradiation in the treatment of stage 4 pressure injuries in a patient with multiple injuries and complete paraplegia. The ward round team consisted of doctor, nurse and rehabilitation therapist was established to comprehensively evaluate the wound condition of the patient. In addition to effective decompression, nutritional support and emotion regulation, Huolong pot comprehensive moxibustion combined with Chinese herbal medicine wound dressing and TDP electromagnetic wave irradiation were carried out to regulate Qi and blood, activate the channels and collaterals, improve the infection control and wound healing of the pressure injuries. (本文总结1例多发伤并完全性截瘫伴4期压力性损伤患者采用火龙罐综合灸联合生肌玉红膏换药、特定电磁波谱(TDP)照射治疗的护理经验。患者入科后由医护康查房小组和压疮小组对伤口进行动态评估, 中医护理小组会诊, 在有效减压、营养支持、情志调护等基础上, 实施火龙罐综合灸联合生肌玉红膏换药、TDP照射中医特色护理, 以温经通络、行气活血、去腐生肌, 控制感染, 促进患者创面愈合。)